Thermal performance and optimum insulation thickness of building walls with different structure materials - Ozel, Meral (Pergamon-Elsevier Science Ltd, 2011)
This study deals with thermal performance and optimum insulation thickness of building walls with different structure materials under dynamic thermal conditions. Thermal performance of building walls constructed of concrete, briquette, brick, blokbims and autoclaved aerated concrete (AAC) is determined for uninsulated and insulated wall structures. Extruded polystyrene (XPS) and expanded polystyrene (EPS) as insulation material are selected. The yearly cooling and heating transmission loads are calculated by using an implicit finite difference method under steady periodic conditions. These loads are used as inputs to an economic model including the cost of insulation material and the present value of energy consumption cost over lifetime of 10 years of the building to determine the optimum insulation thickness. The investigation is carried out for a south-facing wall and the climatic conditions of Elazig, Turkey. Results show that the optimum insulation thicknesses vary between 2 and 8.2 cm, the energy savings vary between 2.78 and 102.16 $/m(2), and the payback periods vary between 132 and 10.33 years depending on five different structure materials and two different insulation materials. Results are compared with the degree-days method. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Thermal performance; Optimum insulation thickness; Heating and cooling loads; Dynamic thermal condition; Energy savings